The phonemicity of glides in Spanish: cambia vs. rocía - Bárkányi, Zsuzsanna (Verbum – Analecta Neolatina, 2002)
In the present article I will argue that there is no need to posit underlying glides in Spanish because the syllabicity of high vowels (i, u) is determined by the stress pattern of the word and the segmental environment of the vowels. I will also argue that non-alternating rising diphthongs and falling diphthongs can uniformly be accounted for in the framework of strict CV (Lowenstamm 1996).